The Effects of Smoking Abstinence on Incentivized Spatial Working Memory. (2nd January 2018) - Geier, Charles; Roberts, Nicole; Lydon-Staley, David
ABSTRACT: Background and Objective: Reward processing and working memory (WM) underlie value-based decision-making; consequently, joint examination of these systems may further our understanding of why smokers choose to smoke again following a quit attempt (relapse). While previous studies have demonstrated altered reward and WM function associated with nicotine exposure, little is known about the effects of abstinence on the joint function of these systems. The current study aims to address this gap. Method: Eighteen daily smokers were tested on a monetarily incentivized memory guided saccade (MGS) task on two separate, counterbalanced occasions, an abstinent and a non-abstinent session. The MGS task is a widely used metric of spatial working memory and enables precise quantification of the effects of rewards and nicotine exposure on behavior. Results: During the non-abstinent session, participants showed increased accuracy of the initial saccade towards the remembered target location on reward vs. neutral trials. Participants also showed increased accuracy of the final saccade towards the target, across incentive types, only during the non-abstinent condition. Discussion and Conclusions: Our observation that rewards improve the accuracy of the initial memory guided saccade during the non-abstinent but not abstinent condition extends a growing literature indicating reduced motivation towards monetary rewards during abstinence. Further, differences in the accuracy of the final corrective saccade during the non-abstinent but not the abstinent condition suggests smoking abstinence-related effects on WM precision beyond those related to incentive motivation (e.g., sustained attention). Significance: This work extends our fundamental understanding of smoking's effects on core affective and cognitive processes.